Green-/NIR-light-controlled rapid photochromism featuring reversible thermally activated delayed fluorescence and photoelectronic switching. Issue 32 (3rd August 2022) - Li, Ziyong; Zhang, Ji-Rui; Tian, Xu-Ke; Yang, Shuren; Chen, Si; Zhou, Hui; Yang, Xiao-Gang
Abstract : Controlled by the alternating irradiation of green and NIR light, difluoroboron modifed dithienylethene shows rapid photochromism and photoelectronic switching. Abstract : Fluorescent dithienylethene-based photochromic materials have been attracting considerable attention owing to their wide applications in biological and materials sciences. However, the limitations of detrimental UV irradiation for photocyclization, short emission lifetime, and inefficient photoresponsive speed still need to be addressed. Herein, a novel dithienylethene photochromic molecule, BFBDTE, has been prepared by the incorporation of a difluoroboron β-diketonate (BF2 bdk) unit. The strong electron acceptor BF2 bdk not only reduces the energy gap of the open isomer, ensuring visible light-controlled fluorescence switching, but also promotes intersystem crossing for the generation of thermally activated delayed fluorescence (TADF). Upon alternating irradiation with green and NIR light, BFBDTE presents a rare example of photochromism, fluorescence and TADF switching in various polar solvents and a poly(methyl methacrylate) (PMMA) film. Meanwhile, it shows rapid and well repeatable cyclization (12 s) and cycloreversion reactions (20 s) in PMMA, accompanied by fast TADF switching within 11 s. Furthermore, photo-electrochemical measurements reveal a remarkable on-off photoelectronic response (photocurrent density ratio: I light / I dark = 684) between the open- and closed-form of BFBDTE . These remarkable merits make BFBDTE promising for photoswitchable molecular devices, optical memory storage systems, NIR detectors, and photoelectric switching.